2013
DOI: 10.1007/s11136-013-0550-2
|View full text |Cite
|
Sign up to set email alerts
|

Joint models for predicting transplant-related mortality from quality of life data

Abstract: Purpose To test whether longitudinally measured health-related quality of life (HRQL) predicts transplant-related mortality (TRM) in pediatric hematopoietic stem cell transplant (HSCT). Methods The predictors of interest were emotional functioning, physical functioning, role functioning, and global HRQL, as rated by the parent about the child up to 6 times over 12 months of follow-up and measured by the Child-Health Ratings Inventories (CHRIs). We used joint models, specifically shared parameter models, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Adverse physical symptoms are common indicators of the health-related quality of life (HRQOL) physical domain [ 12 ]. Earlier studies suggest that poorer physical condition is associated with diminished well-being of patients [ 13 ], a lower psychological domain of HRQOL [ 14 ], higher distress, anxiety and depression [ 13 , 15 18 ], and poorer health prognosis and survival rates [ 19 21 ]. Physical functioning of patients after HSCT is frequently the focus of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Adverse physical symptoms are common indicators of the health-related quality of life (HRQOL) physical domain [ 12 ]. Earlier studies suggest that poorer physical condition is associated with diminished well-being of patients [ 13 ], a lower psychological domain of HRQOL [ 14 ], higher distress, anxiety and depression [ 13 , 15 18 ], and poorer health prognosis and survival rates [ 19 21 ]. Physical functioning of patients after HSCT is frequently the focus of studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its usefulness as a patient-reported outcome, HRQL assessments provide can serve as predictors of future outcomes, such as prognosis and survival (Coates et al, 2000; Gotay et al, 2008; Hsu, Speers, Kennecke, & Cheung, 2017; Kaplan et al, 2007; Khouli et al, 2011; Terrin et al, 2015). However, evidence linking HRQL to future healthcare utilization, particularly in pediatric populations, has been limited (Kephart & Asada, 2009; Lima & Kopec, 2005; Parkerson et al, 2001; Ryan et al, 2013; Seid et al, 2004; Wherry, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior studies have demonstrated HRQL can serve as a predictor of future outcomes, such as prognosis and survival (Coates et al, 2000; Eton et al, 2003; Gotay, Kawamoto, Bottomley, & Efficace, 2008; Kaplan et al, 2007; Kephart & Asada, 2009; Lima & Kopec, 2005; Parkerson Jr, Harrell Jr, Hammond, & Wang, 2001; Ryan et al, 2013; Seid, Varni, Segall, & Kurtin, 2004; Terrin, Rodday, & Parsons, 2015; Wherry, Burns, & Leininger, 2014). Limited studies have shown that HRQL scores also predict healthcare utilization (Kephart & Asada, 2009; Lima & Kopec, 2005; Parkerson et al, 2001; Ryan et al, 2013; Seid et al, 2004; Wherry, et al, 2014); even fewer studies have focused on pediatric populations.…”
mentioning
confidence: 99%
“…The TM in joint modeling for cancer vaccine trials in malignant melanoma has been considered in [9][10][11][12]. The TM models have been also used in quality-of-life studies [13][14][15][16], and in AIDS studies [17][18][19][20][21][22][23]. The SPM models have been used in other types of biomedical applications [24,25].…”
Section: Introductionmentioning
confidence: 99%